Not a silver bullet: social perspectives on desalination and water reuse in Texas - Brannstrom, Christian (2022)
Climate disruptions threaten water systems and undermine economic growth in urban areas. Stakeholder perspectives for desalination and water reuse are not well known in Texas (USA) although utilities are implementing these water augmentation technologies for municipal and industrial purposes. We use a water portfolio-informed deployment of Q-methodology to identify three social perspectives: Diversification is Key, Conservation Before Desalination, and Private Sector Can Do It. We expected to find strongly supportive and opposed social perspectives, but found nuanced and contingent support for desalination and water reuse. Social perspectives were aware of the financial and political costs of desalination and reuse and did not want desalination and water reuse to reduce the importance of protecting currently sources of potable water in Texas. Cross-cutting themes include the predominance of desalination as the policy-relevant water supply alternative and concerns for human capital at levels ranging from desalination plant operators to legal experts.